2015
DOI: 10.1590/0104-1169.0090.2551
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients with oral mucositis: challenges for nursing care

Abstract: OBJECTIVE: to analyze nursing care provided to cancer patients with oral mucositis based on the Nursing Process (NP). METHOD: this exploratory, descriptive, cross-sectional and quantitative study was conducted with 213 patients undergoing chemotherapy and/or radiotherapy in two cancer facilities: one philanthropic and one private service. RESULTS: the participants were mainly female, aged 45.8 years old on average, with up to 11 years of schooling and income of up to one times the minimum wage. Severe mucositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 15 publications
2
26
0
16
Order By: Relevance
“…The occurrence of OM ranges from 40% to 76% in patients undergoing chemotherapy, which increases when chemotherapy is associated with radiation . It is plausible that children have a higher prevalence of OM than adults, which may be related to the rapid cell division found in this population .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of OM ranges from 40% to 76% in patients undergoing chemotherapy, which increases when chemotherapy is associated with radiation . It is plausible that children have a higher prevalence of OM than adults, which may be related to the rapid cell division found in this population .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it has been observed that oral care can reduce the severity and incidence of OM (Coracin et al, ). On the other hand, some reports have shown that oral problems are not adequately addressed in cancer patients undergoing chemotherapy, that these problems are inadequately treated due to being ignored by both doctors and nurses, and that there is a lack of nursing interventions for cancer patients who have oral mucositis (Araújo et al, ; Daniel, Damato, & Johnson, ; Honnor & Law, ). These circumstances may even be at more serious levels in the case of individuals receiving outpatient chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with literature recommending mouthwashes with solutions, such as bicarbonate, aimed at alleviating its symptoms. 17 Moreover, nursing guidelines on oral hygiene maintenance and how to do it is the most effective way to prevent this condition, 18 which was also evidenced in the study. Nonetheless, the definition of the severity criteria of the condition and the establishment of the risk classification to prioritize preventive measures, which are essential elements in this care, were not addressed by the participants.…”
Section: See the Child's Favorites Because The Child Who Is Doing Chmentioning
confidence: 64%